The impact of continuous professional development on teaching quality: a systematic review - Ambon, Josephine; Alias, Bity Salwana; Komariah, Aan; Mansor, Azlin Norhaini (International Journal of Evaluation and Research in Education (IJERE), 2024)
This article explores the impact of continuous professional development (CPD) on teaching quality. The article provides a comprehensive overview of CPD, focusing on pedagogical skills, classroom problem-solving abilities, and the mediating role of leadership within educational institutions. This study used PRISMA approach by analyzing 2,432 English-language publications from 2023 to 2024 taken from the Scopus, Web of Sciences (WoS), and ERIC databases. The data were collected, reviewed, and underwent a peer-review process before a systematic literature review. This article synthesizes findings from final articles (n=24) into five main themes: student perceptions and teaching quality, professional development (PD) and teacher learning, role of leadership in teacher development, assessment and evaluation in teaching, and collaboration and community in teaching. The review reveals that CPD significantly enhances teaching quality by improving pedagogical skills and problem-solving capabilities in the classroom. Furthermore, leadership within educational institutions plays a crucial role in facilitating the positive effects of CPD on teaching quality. By fostering an environment that supports PD, collaborative learning, and reflective practice, educational leaders can amplify the benefits of CPD. This study contributes to the understanding of how CPD and effective leadership together can elevate teaching standards and outcomes, offering valuable insights for policymakers, educators, and academic leaders aiming to enhance educational quality through PD.